Management of Oral Candidiasis in People Living With HIV - Yassir Ahmad Azzaim (Denta Journal Kedokteran Gigi, 2023)
Background: The incidence of HIV/AIDS has increased significantly over the last decade, both globally and in Indonesia. In this situation, the patient has severe impairment in their cellular immunity, making them susceptible to various kinds of opportunistic infections. Oral candidiasis is the most common oral lesion related to HIV/AIDS. Oral candidiasis in people living with HIV (PLHIV) needs to be treated because it can evolve into a systemic infection through the lymphatic system that attacks vital organs. Objective: To know the management of oral candidiasis in PLHIV. Methods: A web-based search was performed via the PubMed, ScienceDirect, and Google Scholar database. Original research and case reports (2018–2023) published in the English language were included to appraise various topics. The number of articles included in the review amounted to 9 articles. Literature Study: Management of patients with oral candidiasis in PLHIV by eliminating predisposing factors, improving oral hygiene, and administering antifungal drugs such as topical agents and/or systemic triazoles. Discussion: In cases of oral candidiasis associated with immunodeficient individuals, topical agents may not be effective in such cases, hence triazole systemic administration is necessary. Oral candidiasis in PLHIV is less responsive to polyene antifungal drugs (nystatin and amphotericin B). Conclusions: Management of oral candidiasis in PLHIV sufferers are eliminating predisposing factors, Improving oral hygiene and stopping habits that can worsen the patient's oral hygiene, administration fluconazole antifungal drugs, giving chlorhexidine gluconate mouthwash, and antiretroviral (ARV) treatment.